1999
DOI: 10.1038/sj.onc.1202976
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the NF-κB pathway by virally encoded Death Effector Domains-containing proteins

Abstract: Death E ector Domains (DEDs) have been known to mediate the recruitment of Caspase 8 and its homologs to the aggregated death-inducing signaling complex (DISC), consisting of the death domain (DD)-containing receptors and various signaling proteins. In addition, several viruses were recently shown to encode proteins with DEDs (also called FLICE inhibitory proteins or vFLIPs) which have the ability of blocking cell death induced by DD-containing receptors. We provide evidence that vFLIPs can also modulate the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
311
3
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(332 citation statements)
references
References 60 publications
17
311
3
1
Order By: Relevance
“…The results obtained indicate that the v-FLIP protein is able to activate, in a dose-dependent manner, an NF-jBdriven reporter gene, as previously described [4,8,14] (Fig. 2C).…”
Section: Combination Of Ifn-b Inducers and V-flip Leads To A Synergissupporting
confidence: 85%
“…The results obtained indicate that the v-FLIP protein is able to activate, in a dose-dependent manner, an NF-jBdriven reporter gene, as previously described [4,8,14] (Fig. 2C).…”
Section: Combination Of Ifn-b Inducers and V-flip Leads To A Synergissupporting
confidence: 85%
“…We have previously demonstrated that unlike K13, vFLIP MC159L, from the molluscum contagiousum virus, lacks the ability to activate the NF-kB pathway (Chaudhary et al, 1999). To confirm the above results and to demonstrate the role of the NF-kB pathway in the acquisition of spindle cell morphology by K13, we infected HUVEC with a control retroviral vector (MIGR2) or vectors encoding K13 and MC159L.…”
mentioning
confidence: 73%
“…K13 protein was originally believed to protect virally infected cells from death receptor-induced apoptosis by preventing the activation of caspase-8 and, as such, was classified as a viral Fas-associated death domain protein-like IL-1b-converting enzyme inhibitory protein (vFLIP) (Bertin et al, 1997;Hu et al, 1997;Thome et al, 1997). However, we have subsequently shown that K13 is a strong inducer of the NF-kB pathway through the activation of the IkB kinase complex and does not function as a caspase-8 inhibitor (Chaudhary et al, 1999;Liu et al, 2002;Matta et al, 2003;Matta and Chaudhary, 2004;Chugh et al, 2005). We and others have further shown that K13 utilizes the NF-kB pathway to promote cellular transformation, cytokine secretion and protection against growth-factor withdrawal-induced apoptosis Sun et al, 2003aSun et al, , b, 2006.…”
mentioning
confidence: 99%
“…K13 protein was originally believed to protect virally infected cells from death receptor-induced apoptosis by blocking the recruitment and/or activation of caspase 8/FLICE and, as such, is commonly referred to as viral FLICE inhibitory proteins (vFLIP) (Bertin et al, 1997;Hu et al, 1997;Thome et al, 1997). We subsequently showed that K13 protein also possesses the ability to activate the NF-kB pathway (Chaudhary et al, 1999b;Liu et al, 2002). As K13 is one of the few HHV-8-encoded proteins to be expressed in latently infected KS spindle cells (Sarid et al, 1998;Sturzl et al, 1999), in this report we have investigated its role in the upregulation of IL-8 expression and secretion and the signaling pathways involved in this process.…”
Section: Introductionmentioning
confidence: 99%